Managing Financial Crisis During Economic Downturn 1997 - 1999 : Experience of Agenda Istimewa Sdn. Bhd. a Developer of Kesuma Lakes Township - Ooi, Ling Hock (1999)
Agenda Istimewa Sdn Bhd, the developer of Kesuma Lakes Township, was doing reasonably well during 1996 and 1997. Everything look bright and good until the South East Asia Financial crisis hit Malaysia in the 4th quarter of 1997. Year 1998 was a chaotic year, the property prices drop by 20% - 40%, the sales not only drop but went into negative (withdrawal), sales forecast, cash flows projection and all other financial commitment could not be meet. The consumer confident drop drastically. The effective interest rate went up to as high as 16% per annum and the future of the company look bleak. Nevertheless Agenda Istimewa Sdn Bhd embark on a strategy to overcome the adversity. By adopting proactive measure to react to the market condition. The company adopt the defensive strategy by doing hard selling. They cut prices to generate turnover, they force the contractors and creditors to accept contra sales and try to conserve cash by managing the project and financial. With the support from the top management, the flexibility of product mix and quick charge in market towards better condition. They seems to turnaround but still more obstacles to cross. For the next 12 months they are short of 25 million for the next 12 months in cash flow and they need to plan and do something now